ASPEK LINGUISTIK DALAM BAHASA INGGRIS DAN BAHASA MELAYU MANADO (SINTAKSIS KONTRASTIF ANALISIS) - SAROINSONG, VITTY JUNIO; PELEALU, HETTY; LOTULUNG, DONALD R. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2019)
ABSTRACTThis research entitled Aspect Linguistik in English language and Manado-Malay language (Contrastive Syntax Analisis). The aims of this research are to identify, to classify, to analyze and also to contrast the aspect in English and Manado Malay language. This research is expected to contribute to the development of linguistics in particular the syntax study and also for those who want to know more about aspects.This research used a descriptive method. The English data were collected from books, while Manado Malay language data were collected from several native speakers who live in Warukus 3 Malalayang 1, Manado and Bible in Manado Language. The writer used Aarts & Aarts’s and Chaer’s theory in analyzing the data and Lado’s theory (1957) in contrasting both languages to find out their differences. The result shows that the kind of apects in English and Manado Malay language are progressive and perfective aspect. The differences in aspects between English and Manado Malay language are in English language the progressive aspect marked by to be + Ving, while in Manado Malay language it is indicated by the prefix 'ba' to express the ongoing event. Perfective aspect in English language are marked by -ed at the end of the verb, while in Manado Malay language the perfective aspect marked by ‘so’. Keywords: Aspect, English, Manado-Malay, Contrastive Syntax Analysis